Analysis of the Impact of Contract Marriages on Tourism in Bogor Puncak - Yoga, Vincensius; Wisesa, Krisna Yoga; Pratama, Wisnu; Jauharie, Kaisar Shauma Rif’at; Farelino, Caesar; Kalfin (Communication in Research and Publications (CRP), 2024)
Continuing against the phenomenon of contract marriages and formulating policies that support tourism sustainability. This monitoring may involve collaboration with various parties, including authorities, public figures, and local tourists. The implementation of policies that support the sustainability of tourism at the Bogor Summit has some implications. First, tourism sustainability can enhance the image of a destination as a safe and quality place. It can attract travelers who are looking for a positive travel experience and reduce the negative impact of the contract marriage phenomenon. Moreover, policies supporting public education about contractual marriage risks can help mitigate this practice. Increased public awareness can prevent contractual marriages and promote values that are consistent with applicable social and legal norms. Tourism development focusing on cultural and natural wealth can also provide attractive alternatives for tourists. By attracting tourists to natural and cultural attractions, local governments can reduce reliance on contractual marriage practices as a major attraction. Overall, the implementation of policies that focus on tourism sustainability can have a long-term positive impact. It can not only boost the local economy through sustainable tourism but also strengthen the social and cultural integrity of the Bogor Puncak community. Bogor Puncak, as a popular tourist destination, faces serious challenges related to the phenomenon of contract marriages. Although these practices provide temporary economic contributions, their negative impact on the social, moral, and image aspects of tourism cannot be ignored. The authorities need to take effective action to address the negative impact. The study provides an in-depth overview of the phenomenon of contract marriage in Bogor Puncak, considering a wide range of perspectives, ranging from tourism, and legal, to social aspects. The study's results identify the positive and negative impact of contractual marriage, its prevalence, trends, and legal perspective in Indonesia. The proposed policy recommendations and implications aim to address the negative impact of contract marriages and support the sustainability of tourism in Bogor Summit. Public education, clear regulations, and sustainable tourism development are key steps that the authorities can take. By implementing a policy focused on tourism sustainability, it is expected that Bogor Puncak will retain its image as an attractive and quality destination, as well as provide sustainable economic benefits to local communities.